Territorial Entrepreneurship: A Driving Force for Sustainable Innovation - ABOFLAN, Yawo Esenam; KPOTCHOU, Koffi; KABO, Kossi; PETRISOR , Alexandru Ionut (Journal of Ecohumanism, 2025)
Achieving sustainability goals in developing countries is crucial because of vulnerabilities related to climate change, capital scarcity and increased investment risks. Entrepreneurship is a means of overcoming the ecological, economic and social problems and challenges in terms of transport, consumption, production, development and food that the continent is facing as a result of the remarkable growth in its urban population. Innovative young companies are proposing solutions that take into account the cultural, social and economic realities of users. This potential for businesses to have an impact on sustainability is limited by the financial difficulties associated with the traditional business development model. Using an approach centred on life in the region, this article highlights the opportunities represented by innovative entrepreneurship in territories in need of sustainability. It aims to stimulate reflection on the need to rethink the economic model for innovative businesses with a sustainable impact, whose solutions need to be widely disseminated by considering other forms of investment. It is therefore suggested that local administrators, be they municipalities, cities or regions, should themselves become entrepreneurs by investing in impact businesses. This article invites to consider territorial entrepreneurship as consider entrepreneurship as a dynamic for anchoring sustainable innovations in regions.